1997
DOI: 10.1016/s0741-5214(97)70196-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase activation: An alternate signaling pathway for sustained vascular smooth muscle contraction

Abstract: These data suggest that the activation of MAP kinase is associated with sustained vascular smooth muscle contractions. Pharmacologic manipulation of MAP kinase activation may lead to new approaches to treat pathologic circumstances of increased vasomotor tone such as vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Previous reports have also suggested that ERK is involved in regulating agonist-induced vasoconstriction. For example, inhibition of MAPK activation has been shown to attenuate not only 5-hydroxytryptamine 2A (Florian and Watts, 1998;Banes et al, 1999) but also angiotensin (Epstein et al, 1997)-and ␣ 1 -AR (DiSalvo et al, 1993) mediated vasoconstriction. Possible mechanisms by which ERK activation has been proposed to affect contractile responses include phosphorylation of caldesmon (Adam et al, 1989;Hedges et al, 2000) or myosin (Jin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also suggested that ERK is involved in regulating agonist-induced vasoconstriction. For example, inhibition of MAPK activation has been shown to attenuate not only 5-hydroxytryptamine 2A (Florian and Watts, 1998;Banes et al, 1999) but also angiotensin (Epstein et al, 1997)-and ␣ 1 -AR (DiSalvo et al, 1993) mediated vasoconstriction. Possible mechanisms by which ERK activation has been proposed to affect contractile responses include phosphorylation of caldesmon (Adam et al, 1989;Hedges et al, 2000) or myosin (Jin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of the Erk MAPK pathway is important to vascular smooth muscle mitogenesis stimulated by 5-HT, 16 and 5-HT 2A receptor-mediated contraction is clearly tyrosine kinase/Erk MAPK dependent. [17][18][19]28,29 In contrast, the involvement of the tyrosine kinase or kinases/Erk MAPK pathway in ET-1-induced contraction is less clear. ET-1 acting at ET A receptors possesses the ability to activate the Erk MAPK pathway in human and rat vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 acting at ET A receptors possesses the ability to activate the Erk MAPK pathway in human and rat vascular smooth muscle. 30,31 Only a few reports demonstrate that ET-1-induced contraction can be blocked by tyrosine kinase inhibitors, 29 and although the MEK inhibitor PD098059 was able to reduce ET-1-induced contraction in the isolated rat uterus, 32 no reports specifically implicate the Erk MAPK pathway in arterial contraction in response to ET-1. Interestingly, the ability of ET-1 to act as a direct mitogen is not universally found in that some investigators report that ET-1 could activate the MAPK pathway in smooth muscle but was a poor mitogen.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, JNK / SAPK and p38 MAPK are implicated in responses to cellular stress, inflammation, and apoptosis. p42 / p44 MAPK may play a role in vascular smooth muscle contraction (11). Moreover, p42 / p44 MAPK may be an important regulator for rabbit basilar artery contraction (12).…”
Section: +mentioning
confidence: 99%